Study of the Hibridation of Ablation Casting and Laser Wire Metal Deposition for Aluminum Alloy 5356 - Ana Isabel Fernández-Calvo; Mikel Madarieta; Ane Solana; Ibon Lizarralde; Mikel Rouco; Carlos Soriano (Crystals)
The rapidly growing field of metal additive manufacturing (AM) has enabled the fabrication of near-net-shape components with complex 3D structures in a more reliable, productive, and sustainable way compared to any other manufacturing process. The productivity of AM could be significantly increased combining conventional and AM technologies. However, the application at an industrial level requires the validation of the AM process itself and the assurance of the soundness of the junction between the substrate and the deposited metal at a sufficiently rapid metal deposition rate. In this work, the validation of additively manufactured samples of Al-5356 alloy was performed. These were manufactured partially via an ablation casting process and partially via laser metal deposition using a metallic wire (LMwD). The deposited material showed low porosity levels, i.e., below 0.04%, and a small number of lack-of-union defects, which are detrimental to the mechanical properties. In the tensile samples centred at the junction between the ablated and deposited materials, it was found that when the AM part of the sample exhibited no lack-of-union defects, the region manufactured using LMwD showed higher strength than the ablation-cast part. These results suggest that the combination of ablation casting and LMwD is a competitive technique for the manufacturing of Al-5356 alloy parts with complex geometries.